ANSWER:
(-7)^2-4*(-7)
=49+28
=77
Hope it helps u! :)
The function for a is (f o g) (x) = 8x^2-10.
Explanation
=========================
I already knew that the g of x is equal to
so I substitute inside of the g of x
=======>
=============>
simplify it
=======>
=========>
Answer:
Step-by-step explanation:
<u>Given</u>
- Q(s) = -4s^3 + 7s^2 - 24;
- s = -4 and 1
<u>Verifying zeroes</u>
Q(-4) =
- -4(-4)^3 + 7(-4)^2 - 24 =
- 256 + 112 - 24 =
- 344
- Incorrect as 344 ≠ 0
Q(1) =
- -4(1)^3 + 7(1)^2 - 24 =
- -12 + 7 - 24 =
- -29
- Incorrect as -29 ≠ 0
Answer:
3
Step-by-step explanation:
First, subtract 4 from both sides. When you do this, that leaves you with: 3x=9. Then, divide 9 by 3 to get x by itself. x=3
Answer:
a. 2 – 8 - [- 4 – (-6 + 3 -9)] X ( -10 ÷2) suprimir los signos de agrupacion
Step-by-step explanation: